2017
DOI: 10.1111/febs.14159
|View full text |Cite
|
Sign up to set email alerts
|

[Fe–S] cluster assembly in the apicoplast and its indispensability in mosquito stages of the malaria parasite

Abstract: The relict plastid (apicoplast) of the malaria parasite is the site for important biochemical pathways and is essential for parasite survival. The sulfur mobilization (SUF) pathway of iron-sulfur [Fe-S] cluster assembly in the apicoplast of Plasmodium spp. is of interest due to its absence in the human host suggesting the possibility of antimalarial intervention through apicoplast [Fe-S] biogenesis. We report biochemical characterization of components of the Plasmodium falciparum apicoplast SUF pathway after t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

3
44
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
6
3

Relationship

1
8

Authors

Journals

citations
Cited by 40 publications
(49 citation statements)
references
References 68 publications
3
44
0
Order By: Relevance
“…Although all the mice inoculated with Spatr cKO sporozoites became patent, genotyping revealed that they were carrying only the nonexcised Spatr locus. Nonexcised Spatr cKO population was also detected in salivary gland sporozoites, EEFs and merosomes suggesting that despite Flp/FRT being an efficient system, some parasites still escape excision as also reported earlier (Charan et al, 2017;Choudhary et al, 2018;Combe et al, 2009;Zhang, Mishra, Sakthivel, Fontoura, & Nussenzweig, 2016;Zhang et al, 2012). Because of the presence of a very small nonexcised Spatr population, we observed breakthrough infection resulting in a 1-1.5 day delay in the prepatent period (PPP).…”
Section: Discussionsupporting
confidence: 80%
“…Although all the mice inoculated with Spatr cKO sporozoites became patent, genotyping revealed that they were carrying only the nonexcised Spatr locus. Nonexcised Spatr cKO population was also detected in salivary gland sporozoites, EEFs and merosomes suggesting that despite Flp/FRT being an efficient system, some parasites still escape excision as also reported earlier (Charan et al, 2017;Choudhary et al, 2018;Combe et al, 2009;Zhang, Mishra, Sakthivel, Fontoura, & Nussenzweig, 2016;Zhang et al, 2012). Because of the presence of a very small nonexcised Spatr population, we observed breakthrough infection resulting in a 1-1.5 day delay in the prepatent period (PPP).…”
Section: Discussionsupporting
confidence: 80%
“…This was demonstrated when disruption of the apicoplast Fe-S cluster synthesis pathway and M A N U S C R I P T A C C E P T E D ACCEPTED MANUSCRIPT 7 subsequent chemical rescue with an isoprenoid byproduct was able to rescue parasites from death, indicating its importance to isoprenoid biosynthesis [35]. Fe-S cluster synthesis was also found to be critical to P. berghei sexual stages when genetic knockouts of a cysteine desulfurase involved in the SUF pathway, SufS, were found to have defective sporozoite development in oocysts [36]. D-cycloserine (DCS) is the only drug reported to have an anti-malarial effect mediated through inhibition of SufS in the apicoplast SUF pathway in P. falciparum [37].…”
Section: Iron-sulfur (Fe-s) Complex Synthesismentioning
confidence: 99%
“…Among apicomplexans, three of the different types of Fe-S cluster assembly machineries can be found (Ali and Nozaki 2013): the mitochondrial ISC machinery, the apicoplast SUF machinery, and the cytosolic CIA machinery. To the best of our knowledge, the only studies on Fe-S cluster assembly machineries in apicomplexans have been focused on the apicoplast-localized SUF machinery in Plasmodium species (Charan et al 2017). These studies have demonstrated the importance of this pathway in the survival of the parasite: the SUF machinery supports the apicoplast-specific apoproteins , some of which are vital for the sustainability of the parasites (Charan et al 2014;Haussig et al 2014).…”
Section: Introductionmentioning
confidence: 99%
“…To the best of our knowledge, the only studies on Fe‐S cluster assembly machineries in apicomplexans have been focused on the apicoplast‐localized SUF machinery in Plasmodium species (Charan et al. ). These studies have demonstrated the importance of this pathway in the survival of the parasite: the SUF machinery supports the apicoplast‐specific apoproteins (Gisselberg et al.…”
mentioning
confidence: 99%